Ovarian Follicles Morphology and Morphometry of Adult Kadaknath and Vanaraja Chicken - Kumar, Vijay; Bharti, Sanjay Kumar; Gautam, Avnish Kumar; Sinha , Manoj Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present experiment was conducted on gross anatomical and histological observation of ovary in twelve laying Kadaknath and  Vanaraja Chicken. Under gross observation the shape of the left ovary was elongated triangular in the form of bunch of grapes in  Kadaknath and Vanaraja chicken. Histological observation of the ovary showed that the division of the ovary in to cortex and medulla  was evident in both the breeds. The surface epithelium was made up of single layer of cuboidal cells with spherical to oval nuclei.  However, squamous epithelium was also noticed at some places. Developing primordial and primary follicles were seen in the outer  cortical zone just beneath the germinal epithelium in both the breeds. Proliferation was noticed in germinal epithelium at several  places and cells were seen migrating from here in to the cortical area. This layer was surrounded by flattened/stromal cells and these  cells formed almost continuous layers.
Keywords: Chicken; Kadaknath; Morphology; Morphometry; Ovarian Follicles, Vanaraja